2002
DOI: 10.1115/1.1513793
|View full text |Cite
|
Sign up to set email alerts
|

Transient and Steady-State Dynamic Finite Element Modeling of Belt-Drives

Abstract: In this study, a dynamic finite element model is developed for pulley belt-drive systems and is employed to determine the transient and steady-state response of a prototypical belt-drive. The belt is modeled using standard truss elements, while the pulleys are modeled using rotating circular constraints, for which the driver pulley’s angular velocity is prescribed. Frictional contact between the pulleys and the belt is modeled using a penalty formulation with frictional contact governed by a Coulomb-like tri-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
68
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 100 publications
(73 citation statements)
references
References 22 publications
4
68
0
1
Order By: Relevance
“…The constitutive relations (5), (6) with the Green-Lagrangian strainε lead to a more complicated expression. Because v > 0 and Q > 0, from (22) we find the minimal value of the velocity in a stationary regime:…”
Section: Stationary Motionmentioning
confidence: 99%
See 1 more Smart Citation
“…The constitutive relations (5), (6) with the Green-Lagrangian strainε lead to a more complicated expression. Because v > 0 and Q > 0, from (22) we find the minimal value of the velocity in a stationary regime:…”
Section: Stationary Motionmentioning
confidence: 99%
“…element method [6,7] or using a lumped parameter model of the belt [8]; see also [9] for recent advances in modeling contact in chain and belt drives. Common problems like computational costs for the contact problem at hand, availability of only time-history data as a result of simulation, unavoidable numerical effect of periodic excitation of the structure as new finite elements or lumped masses are leaving the pulley have motivated Leamy for an application of a perturbation method to a closed-form analysis of unsteady belt drive operation [10].…”
mentioning
confidence: 99%
“…[1], where it is also shown that the research of the belt-drives can be divided into belt-drive mechanics studies and serpentine belt-drive dynamic response studies. According to the authors of Ref.…”
Section: Introductionmentioning
confidence: 98%
“…In this technique, a normal reaction force (Fnormal) is generated when a contact point is in contact with a body (i.e. when the point is inside the body) that is given by [25,26]:…”
Section: Penalty Normal Contact Modelmentioning
confidence: 99%
“…• Normal contact is modeled using a penalty formulation [26,27]. Frictional contact is modeled using an accurate and efficient asperity-based friction model [25].…”
mentioning
confidence: 99%